An unusual presentation of bilateral Hutch diverticula. (23rd May 2014) - Fanning, Deirdre Mary; Morrin, Martina; Power, Richard
Summary: Hutch diverticula are rare congenital diverticula. The general consensus is that they occur secondary to a congenital failure of normal muscle development around the ureteral orifice where Waldeyer sheath anatomically covers the space between the intravesical ureter and muscular layer of the bladder. Our case highlights the radiological appearance of Hutch diverticula and the need for contrast-enhanced imaging to enable accurate evaluation and diagnosis. It illustrates how the presence of periureteric diverticula can contribute to ureteric obstruction and calculus formation; complicate the interpretation of renal tract imaging and the subsequent management of renal calculi.